2008
DOI: 10.1002/app.27898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural and organically modified montmorillonite clays on the properties of polydimethylsiloxane rubber

Abstract: The effects of natural (MT) and organically modified (O-MT) montmorillonite clays on the properties of polydimethylsiloxane (PDMS) rubber were evaluated. Rubber composites with different clay contents were prepared by a compounding procedure in an open two-roll mill, which was followed by a compression-molding step in which the PDMS matrix was peroxide crosslinked. The clay rubber composites were characterized by swelling measurements in toluene, thermogravimetric analyses, X-ray diffraction, scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
2
29
1
Order By: Relevance
“…The ratio remarkably decreased with the silica concentration, and the ratio was even down to 0.486 when the concentration of MCM-41 was 20 wt %, which is almost 60% lower than that of pure PDMS. The silica nanoparticles increased the crosslinking density of PDMS [26]. According to the Flory-Rehner rubber swelling theory [30], the increase of crosslinking density decreased the swelling ratio of PDMS.…”
Section: Swelling Of Pdms/silica Nanocompositesmentioning
confidence: 97%
See 1 more Smart Citation
“…The ratio remarkably decreased with the silica concentration, and the ratio was even down to 0.486 when the concentration of MCM-41 was 20 wt %, which is almost 60% lower than that of pure PDMS. The silica nanoparticles increased the crosslinking density of PDMS [26]. According to the Flory-Rehner rubber swelling theory [30], the increase of crosslinking density decreased the swelling ratio of PDMS.…”
Section: Swelling Of Pdms/silica Nanocompositesmentioning
confidence: 97%
“…Hence the CTE of PDMS can be decreased by adding silica nanoparticles. On the other hand, covalent bonds between silica nanoparticles and PDMS and hydrogen bonds between silica nanoparticles formed [16,26]. The bonds caused large interaction between PDMS and silica nanoparticles, and the interaction restricted the heat deformation of PDMS.…”
Section: The Cte Of Pdms/silica Nanocompositesmentioning
confidence: 99%
“…The average molar mass between cross linking points (M C ) was calculated using the Flory-Rehiner equation for a tetrafunctional polymeric network Equation 3 [18]. The polymer volume fraction (φ pol ) was calculated by Equation 4 [17]. χ was determined as a function of concentration according to [19] Equation 5.…”
Section: Solvent Swellingmentioning
confidence: 99%
“…Following the equilibrium solvent uptake, the samples were removed from toluene and allowed to dry in air for a minimum of 24 hours and re-weighed. The swelling ratio (S R ) of the polymer network was calculated by using Equation 1 [17] and the sol fraction was determined using Equation 2. The average molar mass between cross linking points (M C ) was calculated using the Flory-Rehiner equation for a tetrafunctional polymeric network Equation 3 [18].…”
Section: Solvent Swellingmentioning
confidence: 99%
“…Polymer/clay nanocomposites can solve these problems. Several studies have reported about silicone rubber/MMT nanocomposites (Dong et al, 2006;Kaneko & Yoshida, 2008;Kim, Kim, Shim, & Yoon, 2008). However, there are few studies about silicone/clay nanocomposite.…”
Section: Introductionmentioning
confidence: 96%